Alternative splicing of the metalloprotease ADAMTS17 spacer regulates secretion and modulates autoproteolytic activity. Issue 2 (23rd January 2021) - Balic, Zerina; Misra, Saurav; Willard, Belinda; Reinhardt, Dieter P.; Apte, Suneel S.; Hubmacher, Dirk
Abstract: ADAMTS proteases mediate biosynthesis and breakdown of secreted extracellular matrix (ECM) molecules in numerous physiological and disease processes. In addition to their catalytic domains, ADAMTS proteases contain ancillary domains, which mediate substrate recognition and ECM binding and confer distinctive properties and roles to individual ADAMTS proteases. Although alternative splicing can greatly expand the structural and functional diversity of ADAMTS proteases, it has been infrequently reported and functional consequences have been rarely investigated. Here, we characterize the structural and functional impact of alternative splicing of ADAMTS17, mutations in which cause Weill‐Marchesani syndrome 4. Two novel ADAMTS17 splice variants, ADAMTS17A and ADAMTS17B, were investigated by structural modeling, mass spectrometry, and biochemical approaches. Our results identify a novel disulfide‐bridged insertion in the ADAMTS17A spacer that originates from inclusion of a novel exon. This insertion results in differential autoproteolysis of ADAMTS17, and thus, predicts altered proteolytic activity against other substrates. The second variant, ADAMTS17B, results from an in‐frame exon deletion and prevents ADAMTS17B secretion. Thus, alternative splicing of the ADAMTS spacer significantly regulates the physiologically relevant proteolytic activity of ADAMTS17, either by altering proteolytic specificity (ADAMTS17A) or by altering cellular localization (ADAMTS17B).